Agrobacterium Mediated Stable Integration of Aspergillus niger Pectin Methyl Esterase Gene into Tobacco Cell (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Agrobacterium tumefacience; pectin methyl esterase; transgenic tobacco cells; PCR, CaMV 35S promotorBangladesh j. genet. biotechnol. 5 (1&2): 57-59, 2004 (June & December)